The Impact of Lato-Lato Games on Behavioral Changes in Elementary Children - Wahyu Iskandar (Journal of Contemporary Gender and Child Studies, 2022)
This study aims to identify and obtain information about parents' views of lato-lato games, whether they have an impact on behavior change or not. At present the game lato-lato is a game that is loved by people of all ages, both young and old. The game lato-lato is a game in the form of two small balls or pendulums which are connected to each other by means of a rope which is played simply by hitting the two balls with the palms of the hands to make a loud sound with an up and down motion. The descriptive-qualitative research method was used in this study which aims to provide an overview and present information about something according to the conditions at that time. The data collection technique in this study was through interviews and observations around the Matauli Pandan house complex. The results showed that children who play lato-lato tend to be more active in interacting and socializing, considering that this game is more fun when played together. In addition, with increasing social interaction, children also reduce the intensity of children's use and dependence on gadgets. Therefore, if it is still under good supervision from parents, this game will help children to improve their motor and cognitive abilities, as well as their social skills.